2014
DOI: 10.1016/j.jep.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Croton campestris A. St-Hill in different ulcer models in rodents: Evidence for the involvement of nitric oxide and prostaglandins

Abstract: Taking together, these results suggest that the antiulcer activity of CCRE is dependent of NO and prostaglandin pathways possibly due to its ability to stimulate the synthesis of NO, and activation of endogenous prostaglandin production. Therefore, the use of CCRE in traditional Brazilian medicine against gastric disorders has a scientific basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 29 publications
1
8
0
8
Order By: Relevance
“…Moreover, quercetrin (2) protected skin from UVB-induced inflammation (Yin et al, 2013), displayed antioxidant (Aderogba, Okoh, Idowu, 2005;Tai et al, 2014) and antileishmanial activities (Muzitano et al, 2006b), showed antiproliferative and apoptotic effects in colon cancer cells (Cincin et al, 2015), demonstrated gastroprotective actions (Mota et al, 2009) and showed intestinal anti-inflammatory effects (Camuesco et al, 2004). Júnior et al, (2014) reported that quercitrin was present in Croton campestris extracts at 2.34% and might be involved in gastroprotective activities against ethanol, acidified ethanol-, and indomethacin-induced gastric lesions. This antiulcer effect seems to be mediated by NO and endogenous prostaglandin pathways.…”
mentioning
confidence: 99%
“…Moreover, quercetrin (2) protected skin from UVB-induced inflammation (Yin et al, 2013), displayed antioxidant (Aderogba, Okoh, Idowu, 2005;Tai et al, 2014) and antileishmanial activities (Muzitano et al, 2006b), showed antiproliferative and apoptotic effects in colon cancer cells (Cincin et al, 2015), demonstrated gastroprotective actions (Mota et al, 2009) and showed intestinal anti-inflammatory effects (Camuesco et al, 2004). Júnior et al, (2014) reported that quercitrin was present in Croton campestris extracts at 2.34% and might be involved in gastroprotective activities against ethanol, acidified ethanol-, and indomethacin-induced gastric lesions. This antiulcer effect seems to be mediated by NO and endogenous prostaglandin pathways.…”
mentioning
confidence: 99%
“…Una motilidad gastrointestinal incrementada podría promover la protección gástrica al acelerar el vaciamiento gástrico de aquellos agentes dañinos de la mucosa [9]. Por otra parte, la disminución de la motilidad gástrica podría ser un mecanismo de gastroprotección, pues implica menor exposición al agente corrosivo en términos de área superficial [1].…”
Section: Aqueous Extract Of Licaniaunclassified
“…Posteriormente, trascurrida una hora, se procedió a anestesiar a las ratas con vapores de éter dietílico; se practicó laparatomía y se extrajo el estómago, el cual fue abierto por la curvatura mayor. Para el análisis macroscó-pico de los estómagos, se obtuvieron las imágenes digitalizadas y se midió del área de lesión gástrica en mm 2 por medio del software ImageJ del National Institute of Health (NIH) (13) . El cálculo del porcentaje de protección de la mucosa gástrica fue expresado según Sandoval y col. (14) Se realizó también el estudio microscópico, para lo cual cada tejido gástrico fue conservado en formol al 10% para su estudio histopatológico.…”
Section: Métodosunclassified